Cut-off Values of Bacteriuria and Leukocyturia to Diagnose Urinary Tract Infection in Patients Aged 0-12 Months - Rahmania Chandra Savitri; Dian Ariningrum; Yusuf Ari Mashuri (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Urinary Tract Infections (UTIs) are among the most common bacterial infections in the community, including infants and children. Urine culture is the gold standard test for UTI detection, but it is expensive, impractical and takes a long time. At present, automated urinalysis methods have been used by many for UTI screening. The aim of this study was to determine the cut-off values of leukocyturia and bacteriuria using flow cytometry (FCM) method using automated urinalyzer Sysmex UX-2000 for screening of UTI in infant patients aged 0-12 months. A cross-sectional study with a diagnostic test was conducted at the Dr. Moewardi Hospital in Surakarta on August - October 2019. A total of 34 patients underwent urine culture examination and automatic urine analyzer using Sysmex UX-2000. Cut-off values of leukocyturia and bacteriuria were determined from the ROC curve followed by determination of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy and likelihood ratio. The cut-off value for leukocyturia in infant patients aged 0-12 months was 46.2 cells/μL with a sensitivity value of 88%, specificity 68%, PPV 50%, NPV 94%, accuracy 73% and likelihood ratio 2.77. The cut-off value of bacteriuria in infant patients aged 0-12 months was 247.6 cells/μL with a sensitivity value of 66%, specificity 64%, PPV 40%, NPV 84%, accuracy 64% and likelihood ratio 1.85. Cut-off values of leukocyturia and bacteriuria using automatic urine analyzer Sysmex UX-2000 with negative predictive value (NPV) >80% can be used for UTI screening in infant patients aged 0-12 months.